Radical Institutional Economics and Fakery for the 21st Century - Svetlana G. Kirdina-Chandler (Журнал институциональных исследований, 2018)
The article summarises some results of the discussions about radical institutional economics (RIE) for the 21st century. The discussions took place at the 38th Conference of the Association for Institutional Thought, held in April 2017 (San Francisco, California, US). The contribution of radical institutional economists of the 1990s in the development of institutional thought is presented in the article. The works of William M. Dugger – the founder of RIE – are stressed, as well as the roles of other radical institutionalists such as Edythe Miller, J. Ron Stanfield, Ron Phillips, Dell Champlin, Janice Peterson, Charles Whalen, Doug Brown, Rick Tilman, Louis Junker and Howard Sherman. The reasons for the reintroduction of radical institutional economics onto the agenda in the modern US are considered, among them being the increasing fakery in economies and the growth of inequality in incomes and distribution of economic benefits. The article then suggests a hypothesis that an external factor in the radicalisation of science and public consciousness in Western and other countries is associated with a change in world leaders and poles of growth, and is a turning point in history. It is argued that the power of countries in which the X-matrix dominates is beginning to surpass the influence of countries where the Y-matrix dominates.